2012
DOI: 10.1002/crat.201200005
|View full text |Cite
|
Sign up to set email alerts
|

Polarity determination of rough and smooth surface grains in AlN crystals

Abstract: The polarity of rough and smooth grains in textured aluminum nitride boules were analyzed by transmission electron microscopy. Specifically, convergent beam electron diffraction method was applied to determine polarity. The grains corresponding to smooth and rough surfaces were identified as having Al and N polarities, respectively. Aluminum oxide (Al2O3) was observed to form at the grain boundaries. The oxide may precipitate due to the low mutual solubility between Al2O3 and AlN at the high crystal growth tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…18−20 Control of polarity is also essential for device design due to the strong polarization-induced internal electric fields. 21 The experimental results of Filip et al 19 in a tungsten setup using Al-polar, Npolar, and mixed-polar seeds showed that the colorless or light brown Al-polar crystals have better light transmission than the dark brown N-polar crystals. In general, the growth of N-polar crystals is more likely to introduce carbon/oxygen impurities and point defects, which result in low UV transmission, although N-polar growth can usually maintain a stable and uniform step-flow growth mechanism.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…18−20 Control of polarity is also essential for device design due to the strong polarization-induced internal electric fields. 21 The experimental results of Filip et al 19 in a tungsten setup using Al-polar, Npolar, and mixed-polar seeds showed that the colorless or light brown Al-polar crystals have better light transmission than the dark brown N-polar crystals. In general, the growth of N-polar crystals is more likely to introduce carbon/oxygen impurities and point defects, which result in low UV transmission, although N-polar growth can usually maintain a stable and uniform step-flow growth mechanism.…”
Section: Introductionmentioning
confidence: 98%
“…It is reported that the growth setup, growth process, and seed polarities have a significant effect on the UV transparency of AlN crystals. In particular, crystal polarity is a key factor in controlling the AlN surface morphology and growth mechanism, since it strongly impacts the incorporation of unintentionally doped impurities (O, C, and Si) in AlN crystals and their interplay with intrinsic point defects and, hence, the electrical and optical properties of AlN. Control of polarity is also essential for device design due to the strong polarization-induced internal electric fields . The experimental results of Filip et al in a tungsten setup using Al-polar, N-polar, and mixed-polar seeds showed that the colorless or light brown Al-polar crystals have better light transmission than the dark brown N-polar crystals.…”
Section: Introductionmentioning
confidence: 99%